Investigating an early Islamic landscape on Kuwait Bay: the archaeology of historical Kadhima - Blair, Andrew; al-Duwīsh, Sultan M.; Kennet, Derek (Proceedings of the Seminar for Arabian Studies, 2012)
In volume 41 of the Proceedings of the Seminar for Arabian Studies the authors introduced the Kadhima Project, an investigation of the early Islamic archaeology of the western coast of Kuwait Bay. The present paper introduces the findings of the second season of research, focusing on three key types of site: a courtyard building which is probably a fort; small, localized scatters of torpedo jars, which recur frequently; and a number of settlements of varying sizes. Following a detailed examination of the archaeology of these three classes of site, the authors outline a provisional chronology for the occupation of Kuwait Bay in the late pre-Islamic and early Islamic periods. It is argued that an increase in the intensity of maritime and overland trade between the fifth and seventh centuries coincides with a settlement peak in the eighth century, and that the entire landscape then appears to have been rapidly abandoned by the mid-ninth century. While this occupation trajectory has a local character, the expansion in the eighth century appears to mirror contemporary developments elsewhere in eastern Arabia.